Association of KIM-1 (HAVCR1) Expression with the Tumor Immune Microenvironment in Clear Cell Renal Cell Carcinoma - Vlachostergios, Panagiotis J.; Karathanasis, Athanasios; Karasavvidou, Foteini; Tzortzis, Vassilios (Current Gene Therapy, 2025)
<span class=
Keywords: biomarker